Branding Strategy On Instagram: A Case Study Of A Creative Digital Marketing Agency- Jt Digitally - Theresa Karlianti; Dindin Dimyati (Universitas Telkom, 2025)
A branding strategy is a communication plan used by a corporation to establish and maintain a brand. Branding strategy has fundamentally changed in the digital arena due to the rapid development of technology. One of the channels is social media, which has the potential to reach a big number of people at a low cost and with no restrictions. JT Digitally, a Digital Marketing Agency, is an organisation that uses social media as a branding strategy tool and provides services to manage business branding on social media. The purpose of this study was to investigate and analyse the process of JT's digital branding strategy on Instagram. The interpretivism paradigm and case study approach are used in this study's qualitative research. The researcher employs an in-depth interview and observations to acquire data. According to the findings of this study, JT Digitally uses Instagram to build a branding strategy by using some of its elements such as profile, followers, post, caption, hashtag, Instagram Story, and Instagram Ads.